If fx = 1x2∫3x2t - 3f'tdt, then f't, then f'(3) is equal to
- 1 2
- 13
12
13
∫dxx + 100x + 99 = fx + c ⇒ fx
2(x + 100)1/2
3(x + 100)1/2
2tan-1x + 99
2tan-1x + 100
∫3 - x21 - 2x + x2exdx = exfx + c ⇒ fx
1 + x1 - x
1 - x1 + x
1 - xx - 1
x - 11 + x
∫cotxsinxcosxdx = - fx + c ⇒ fx
2tanx
- 2tanx
- 2cotx
2cotx
∫- π2π2log2 - sinθ2 + sinθdθ is equal to
0
1
2
- 1
∫022x - 22x - x2dx is equal to
3
4
If ∫sinxcosx1 + cosxdx = f(x) + c, then f(x) is equal to
log1 + cosxcosx
logcosx1 + cosx
logsinx1 + sinx
log1 + sinxsinx
∫x49tan-1x501 + x100dx = ktan-1x502 + c, then k is equal to
150
- 150
1100
- 1100
∫0π2200sinx + 100cosxsinx + cosxdx is equal to
50π
25π
75π
150π
∫0πθsinθ1 + cos2θdθ is equal to
π22
π23
π2
π24